2017
DOI: 10.1177/0034355217724341
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing a Digital Career Literacy Training for Vocational Rehabilitation Professionals

Abstract: Digital career literacy encompasses the skills needed to find and maintain employment in the modern job market. Unfortunately, many state vocational rehabilitation (VR) professionals report feeling unprepared to help their consumers with digital career literacy tasks. To address this gap, we developed and tested five training webinars with VR professionals in Montana, Alabama, and Washington. We randomly assigned VR offices to intervention or control group. VR professionals in the intervention group received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…The increasing use of webinars in educational contexts was followed by studies that have examined the effectiveness of webinars in higher education and professional training under various circumstances (e.g., Nelson, 2010;Stout et al, 2012;Nicklen et al, 2016;Goe et al, 2018;Gegenfurtner et al, 2019c). According to Phipps and Merisotis (1999), research on the effectiveness of distance education typically includes measures of student outcomes (e.g., grades and test scores) and overall satisfaction.…”
Section: The Evaluation Of Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing use of webinars in educational contexts was followed by studies that have examined the effectiveness of webinars in higher education and professional training under various circumstances (e.g., Nelson, 2010;Stout et al, 2012;Nicklen et al, 2016;Goe et al, 2018;Gegenfurtner et al, 2019c). According to Phipps and Merisotis (1999), research on the effectiveness of distance education typically includes measures of student outcomes (e.g., grades and test scores) and overall satisfaction.…”
Section: The Evaluation Of Learning Environmentsmentioning
confidence: 99%
“…The middle of the 1990s witnessed the slow advent of Internet-based education and early applications of online distance learning (Alnabelsi et al, 2015). Since then, there has been a significant increase in the number of available e-learning resources and educational technologies (Ruiz et al, 2006;Gegenfurtner et al, 2019b;Testers et al, 2019), which have gained more importance in the higher education and professional training contexts (Wang and Hsu, 2008;Nelson, 2010;Siewiorek and Gegenfurtner, 2010;Stout et al, 2012;Knogler et al, 2013;McMahon-Howard and Reimers, 2013;Olson and McCracken, 2015;Testers et al, 2015;McKinney, 2017;Goe et al, 2018). To date, various possibilities regarding the implementation of e-learning in educational contexts exist, one of which is the use of webinars-a prototypical form of synchronous online courses.…”
Section: Introductionmentioning
confidence: 99%
“…Digitalization is a global trend that has also transformed the way in which training and adult education is designed, delivered and implemented (Bell et al , ; Gegenfurtner et al , ; Goe et al , ; Martin et al , ; McKinney, ; Schmid et al , ; Testers et al , ; Testers et al , ). Among the digital tools and infrastructures for training, webinars are commonly applied in distance education and blended learning training programs.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of clear guidelines, counselors may feel unprepared to incorporate social media into counseling practice. Data from a study about social media use among counseling staff ( n = 1,447) indicated that only 28% of counselors feel prepared to assist consumers with improving their online reputations and only 31% feel prepared to assist them with online professional development activities (Goe & Ipsen, 2016). In part, this may relate to concerns over ethics in counseling practice or lack of clear procedures or guidelines for working with consumers in online job search activities (Barros-Bailey & Saunders, 2010; Chapin & Byrne, 2013; Lehmann & Crimando, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data, however, indicate that online strategies are limited in VR practice. A recent study about counselor use of social media in the VR setting ( n = 1,432 counselors representing 32 agencies) found that 40% were blocked from using some or all social media sites while at work and only 43.3% used social media for any work activity (Goe & Ipsen, 2016). Despite low use rates, 37% of respondents said they had participated in training about social media use though work, and receiving training was significantly associated with higher reported rates of preparedness to help consumers (a) research job opportunities, (b) develop skills for professional networking, (c) improve consumer online reputations, and (d) address issues of disability disclosure on social media sites.…”
Section: Social Media Use In Vocational Rehabilitationmentioning
confidence: 99%